Induction of twin pregnancy: a tool for sustainability in beef cattle - Bazzo, Karime Chukr; Andreazzi, Marcia Aparecida; Cavalieri, Fábio Luiz Bim; Silva, Karoline de Souza; Santos, José Maurício Gonçalves dos (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
Beef cattle stand out in the national agribusiness sector; however the forms of production must seek to be economically and environmentally sustainable. In this area, the use of reproduction biotechnologies, such as the induction of twin pregnancies which can increase meat production per area, is necessary. Thus, the objective of this study was to evaluate this technique of inducing twin pregnancy in cattle through double embryo transfer. The study was conducted at Unicesumar Farm and 100 bovine recipients, heifers and cows, mixed breed, were used, divided into groups: G1 – implanted females with 1 embryo and G2 – implanted females with 2 embryos. Recipients were synchronized and, on D17, implanted with 1 or 2 Wagyu embryos produced in vitro, according to the experimental group. Pregnancy rate at 30 and 60 days, parturition rate, occurrence of retained placenta and dystocia, and calf weight both at birth and at 30 days of age were evaluated. The double transfer of embryos improved the pregnancy rate at 30 and 60 days of gestation (p